Formulation and Evaluation of Halal Cosmetic Product Deodorant Spray from Lignin Nanoparticle of Palm Kernel Shell - Nurbaiti, Nurbaiti; Arif, Muhammad; Afdal, Afdal; Ayu, Putri; Nabila, Zahra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Halal cosmetics, including the use of deodorants, have gained substantial attention due to their adherence to ethical, religious, and health-related standards. The lignin extracted from palm oil shells possesses antimicrobial properties, making it a promising candidate for deodorant formulation. This study aimed to evaluate a deodorant formulation incorporating nanoparticle of palm shell lignin and to analyze it as raw material of halal cosmetic. The lignin was synthesized and characterized prior to its incorporation into the deodorant base. The formulated product was then evaluated for its physicochemical properties such as pH, homogeneity, and spreadability. Results showed that palm shell particles exhibited a lignin wavelength of 0.275 nm, an average particle size of 1000 nanometers, and physical properties suitable for cosmetic products. While the evaluation results were promising, further research is needed to optimize the formulation. Variables that could be modified include lignin concentration, type and quantity of additives, and manufacturing method. Palm lignin nanoparticles are a viable and promising material as a raw ingredient for halal cosmetics.Keywords: Halal cosmetic; palm oil shell; deodorant; nanoparticle; lignin